PENGARUH DOSIS PUPUK KANDANG AYAM DAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL SELADA (Lactuca sativa L) - Andrie Suprayogi; Dukat Dukat; Ismail Ismail (Agroswagati Jurnal Agronomi, 2019)
The experiment was conducted to know the effect of chicken manure doses and nitrogen fertilizers on growth and yield of lettuce (Lactuca sativa L). The experiment was conducted at Kutawaringin Village, Selajambe District, Kuningan, West Java Province, from March until May 2018. The experimnetal design was used Randomized Completely Block Design (RBD) with factorial pattern. Each treatment was repeated three times. The treatment consisted two factors. The first factor was ratesÂ  of chicken manure that consisted four levels : K1 (0 ton/ha), K2 (10 ton/ha), K3 (20 ton/ha), K4 (30 ton/ha), while the second factor was nitrogen fertilizers rates which consist three levels : N1 (77 kg/ha), N2 (100 kg/ha), N3 (123 kg/ha). The result showed that there was an interaction effect between chicken manure doses and nitrogen fertilizers on root volume (28 days after planting), total weight per plant, total weight per plot, and total biomass. Independently, chicken manure doses gave significant effect of plant high, number of leafs, leaf area, relative growth rates (28 and 35 days after planting). While nitrogen fertilizers rates effected plant height, number of leaves, leaf area, net assimilation rates (21 days after planting), relative growth rate (21 and 28 days after planting), root volume (35 days after planting). Chicken manure doses 20 ton/ha and nitrogen fertilizers doses 123 kg/ha gave the best result on total weight per plant and per plot which produces 30,56 g per plant and 638,38 g per plot (2,5 ton/ha).